Respuesta :

Answer:

Step-by-step explanation:

1) y  = 2x  ----------(I)

x + y = 6 -----------(II)

Plug in y =2x in equation (II)

x + 2x = 6        {Add like terms}

  3x    = 6

       x = 6/3

      x = 2

Plugin x = 2 in (I)

 y = 2*2

y = 4

Check:

     LHS = x +y

             = 2 + 4

            = 6  = RHS

2)5x + 10y = 3 ------------(I)

x = (-1/2) y     ------------(II)

Substitute x = (-1/2)y in (I)

[tex]5*\frac{-1}{2}y + 10y = 3\\\\\frac{-5}{2}y+ \frac{10*2}{1*2}y = 3\\\\\frac{-5}{2}y+\frac{20}{2}y=3\\\\\frac{-5+20}{2}y = 3\\\\\frac{15}{2}y=3\\\\ y = 3*\frac{2}{15}\\\\ y = \frac{2}{5}[/tex]

Substitute y = (2/5) in equation (II)

[tex]x = \frac{-1}{2}*\frac{2}{5}\\\\x = \frac{-1}{5}[/tex]

Check:

Substitute x and y value in equation (I)

[tex]LHS = 5*\frac{-1}{5}+10*\frac{2}{5}\\\\ = -1 + 2*2\\\\ = -1 + 4\\ = 3 = RHS[/tex]

3) y - x = 3x + 2

        y = 3x + 2 + x

         y = 4x + 2 ---------------(I)

2x + 2y = 14 - y

2x + 2y +y = 14

2x + 3y = 14     ------------------(II)

Substitute y = 4x + 2 in equation (II)

2x + 3(4x +2) = 14

2x + 3*4x + 3*2 = 14

2x + 12x + 6 = 14

        14x + 6 = 14

              14x = 14 - 6

              14x = 8

                 x = 8/14

            x = 4/7

Substitute 'x' value in (I)

[tex]y = 4*\frac{4}{7} +2\\\\y = \frac{16}{7}+2\\\\y= \frac{16}{7}+\frac{2*7}{1*7}\\\\y=\frac{16}{7}+\frac{14}{7}\\\\y=\frac{30}{7}[/tex]

Check:

[tex]LHS = 2x + 3y\\\\ = 2*\frac{4}{7}+3*\frac{30}{7}\\\\ = \frac{8}{7}+\frac{90}{7}\\\\=\frac{8+90}{7}\\\\=\frac{98}{7}\\\\=14 = RHS[/tex]